A scoping review of the conceptualisations of food justice. Issue 4 (23rd April 2023) - Murray, Sandra; Gale, Fred; Adams, David; Dalton, Lisa
Abstract: Objective: The emerging concept of 'food justice' describes a social movement and a set of principles. It align with the goals of social justice, demanding recognition of human rights, equal opportunity, fair treatment and is participatory and community specific. The aim of this study was to investigate the conceptualisation of food justice and to explore how community participation is positioned in food justice scholarship. Design: A scoping review of peer-reviewed literature was conducted using the term 'food justice'. This study used a five-step scoping review protocol. The databases included Scopus, Web of Science and Medline (OVID). Data were extracted on country of origin, research discipline, study type and conceptualisations of food justice. Reflexive thematic analysis was used to identify the themes. Results: The search identified 546 abstracts of which ninety peer-reviewed studies met the inclusion criteria. Thematic analysis identified five themes of food justice across these ninety studies: (1) social equity, (2) food security, (3) food systems transformation, (4) community participation and agency and (5) environmental sustainability. Conclusions: Current conceptualisations of food justice are evolving. Together, these five themes, using the term food justice, embrace a more holistic and structural view of the food system. They emphasise healthy, sustainable and equitable food as a human right and acknowledge the need to address structural barriers to that right. Community participation and agency in food justice decision-making is critical for transformative change towards a healthy, sustainable, and more just food system.